Rancang Bangun Sistem Manajemen Layanan Pemeriksaan Air Berbasis Web di UPTD Laboratorium Kesehatan Kota Bukittinggi - Ahmad Fauzi; Domi Sepri; Sandra Dewi (G-Tech: Jurnal Teknologi Terapan, 2023)
Information technology in public services not only converts work that was originally done manually into digital form, but is also able to make the work carried out by public service providers more effective and efficient. The aim of this research is to create a web-based water examination management system at the Bukittinggi City Health Laboratory. This website was created so that consumers can order and monitor their orders by online. The website development process in this research uses the Software Development Life Cycle (SDLC) - Waterative Model. Website quality testing is carried out by testing it with various kinds of internet browsers, both by using internet browsers on mobile phones and desktops. The results of website testing show that the application can run optimally on various kinds of internet browsers.